2020
DOI: 10.1155/2020/9327868
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features, Treatment Strategy, and Prognosis of Primary Non-Hodgkin’s Lymphoma of the Duodenum: A SEER Database Analysis

Abstract: Objective. Primary duodenum lymphoma (PDL) is extremely rare with limited data available in the literature. In this study, we sought to describe clinical features and identify factors affecting survival in patients with PDL using a large population cohort. Methods. The Surveillance, Epidemiology, and End Results (SEER) database was queried from 1998 to 2015. Results. A total of 1060 cases of PDLs were identified. Clinicopathological features as well as survival data of PDLs were analyzed and compared with 1057… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…DLBCL and BL had similar incidence in small and large intestine, whereas MALTOMA and Mantle cell lymphoma was more common in the large intestine (Table 2). Similar findings were seen in previous studies comprising data from multiple centers (12,14,15). While the median OS of primary intestinal T-cell lymphoma was 6 months, and PI-DLBCL 71 months, it was not reached in follicular lymphoma and was 165 months in MALToma.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…DLBCL and BL had similar incidence in small and large intestine, whereas MALTOMA and Mantle cell lymphoma was more common in the large intestine (Table 2). Similar findings were seen in previous studies comprising data from multiple centers (12,14,15). While the median OS of primary intestinal T-cell lymphoma was 6 months, and PI-DLBCL 71 months, it was not reached in follicular lymphoma and was 165 months in MALToma.…”
Section: Discussionsupporting
confidence: 91%
“…This is the only study which has reported population-based age-adjusted incidence rate with incidence rate ratio close to twice for male compared to female, 0.62 times for non-Hispanic black and 0.92 times for Hispanic patients compared to non-Hispanic white population. In the previous studies, the number of reported cases were almost twice in the males for the eastern Asian population to 1.5 times in German and North American populations, which were seen in our patient group as well (9,11,12).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Survival information was measured in months rather than exact days. For this reason and given the exclusion of patients with only autopsy or death certificates, the surviving time of 0 months was regarded as 0.5 month to enroll any patient who died within 1 month of diagnosis 24,25…”
Section: Methodsmentioning
confidence: 99%
“…For this reason and given the exclusion of patients with only autopsy or death certificates, the surviving time of 0 months was regarded as 0.5 month to enroll any patient who died within 1 month of diagnosis. 24,25 As SEER is available to the public and this study does not identify patient data, no ethical approval from the Institutional Review Board was needed.…”
Section: Data Collection and Codingmentioning
confidence: 99%